An experimental investigation of the draw resonance in film casting of polypropylene melts - Grieß, Hans Jürgen; Münstedt, Helmut; Burghelea, Teodor; Schubert, Dirk W. (Book of Abstracts, 2012)

An in situ investigation of the draw resonance phenomenon in film casting of a polypropylene melt - Burghelea, Teodor I.; Grieß, Hans Jürgen; Münstedt, Helmut (Journal of Non-Newtonian Fluid Mechanics, 2012)
An experimental investigation of the stability of the casting process of a polypropylene film is presented. By combined in situ measurements of the width of the cast film and Digital Particle Image Velocimetry (DPIV) measurements of the velocity distributions within the polymer film, several flow regimes are identified: stable, oscillatory and chaotic. Measurements of the velocity distribution along and across the extruded film corresponding to each drawing regime are presented. The intermittent physical rupture of the film's edges observed within the chaotic drawing regime is explained by the emergence of a " V-shaped" region of high axial gradients of the axial velocity component which indicates a highly inhomogeneous distribution of tensile stresses.By measurements of the statistics of the fluctuations of both the film's width and velocity a continuous (second order) imperfect bifurcation towards oscillatory states is found. The fluctuation data acquired before the chaotic regime is reached can be fitted by the stationary Landau-Ginsburg equation. The observation of a stable limit cycle at the onset of the bifurcation identifies it as a supercritical Hopf bifurcation. The experimentally found scaling of the onset and amplitude of the bifurcation with the Weissenberg number indicates that elasticity destabilizes the drawing process. This can be explained by the thinning behavior of the material in both shear and extension.The spectral analysis of the fluctuations of both film's width and point-wise velocity provides a quantitative description of the harmonics excited beyond the bifurcation point. The transition to chaotic states is accompanied by a major reorganization of the power spectra consistent with a period doubling bifurcation of a stable limit cycle. © 2012 Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Chaos; Coat hanger die; Draw resonance; Film casting; Imperfect bifurcation

Flow behavior of polypropylenes with different molecular structures in a coat-hanger die - Grieß, Hans Jürgen; Münstedt, Helmut (Polymer Engineering and Science, 2012)
An experimental investigation of the flow behavior of three polypropylene melts with different molecular structures during extrusion through a coat-hanger die is presented. Two linear and one long-chain branched material, rheologically characterized in shear and elongation, were investigated. Using laser-Doppler velocimeter measurements of the velocity profiles across the gap height were performed at five various locations along the die. The uniformity of the velocity distribution along the die has been assessed using the maximum velocities v0 of the corresponding velocity profiles across the gap. The velocity distribution along the die changes with throughput and temperature. Regarding the rheological properties, it was found that the power-law index of the viscosity as a function of shear rate has a decisive influence on the uniformity of flow but that the pronounced strain hardening in elongation typical of the long-chain branched polypropylene is not reflected by the velocity distribution along the die. Copyright © 2012 Society of Plastics Engineers.
Created from Fastlane, Scopus look-up

Velocity measurements on a polypropylene melt during extrusion through a flat coat-hanger die - Grieß, Hans Jürgen; Burghelea, Teodor; Münstedt, Helmut (Polymer Engineering and Science, 2012)
An experimental investigation of various flow regimes observed during the extrusion of a polypropylene melt through a flat coat-hanger die by laser-Doppler velocimetry (LDV) is presented. LDV measurements of the velocity profiles across the gap of the die at various locations along the die reveal three different extrusion regimes. At small wall shear stresses, the velocity profiles can be fitted by symmetrical curves with the velocities becoming zero at the die walls. These profiles are not uniformly distributed along the die. An increase of the wall shear stress reveals a second flow regime characterized by a uniform distribution of the velocity profiles along the die. As the wall shear stress is increased even further, a third flow regime characterized by wall slip on the glass windows is observed. This flow regime is systematically characterized by measurements of the slip velocities at various temperatures and throughputs. The maximum velocities along the die are taken to assess the uniformity of flow which decisively influences the thickness of the extruded film. By measuring velocity profiles, at different throughput, and temperatures, the conditions for constant velocities along the die were determined. © 2011 Society of Plastics Engineers.
Created from Fastlane, Scopus look-up